Black Sea GIS developed in MHI - Zhuk, Elena; Khaliulin, Alexey Kh; Zodiatis, George; Nikolaidis, Andreas; Isaeva, Elena (My University, 2016)
The work aims at creating the Black Sea geoinformation system (GIS) and complementing it with a model bank. The software for data access and visualization was developed using client server architecture. A map service based on MapServer and MySQL data management system were chosen for the Black Sea GIS. Php-modules and python-scripts are used to provide data access, processing, and exchange between the client application and the server. According to the basic data types, the module structure of GIS was developed. Each type of data is matched to a module which allows selection and visualization of the data. At present, a GIS complement with a model bank (the models build in to the GIS) and users' models (programs launched on users' PCs but receiving and displaying data via GIS) is developed.
Keywords: Bank of models; Black sea; Climatic atlas; Geoinformation system; Oceanographic data; Remote-sensing data